Intensity Of Watching English Movies On Television And Its Relation To Vocabulary Acquisition - Ekasari, Desie, Drs. Sigit Haryanto, M.Hum, Koesoema Ratih, S.Pd., M.Hum (2013)
Television has a great impact in the field of education. This is the reason why intensity of watching English movies on television and its relation to vocabulary acquisition are taken as the objects of this study. The objective is to find out the relationship between intensity of watching English movies on television and vocabulary acquisition. In this research, the writer takes 50 students. The writer takes all the population as the sample because the subject is less than one hundred. In this case the writer uses two kinds of instrument: the first instrument is test, and the second instrument is questionnaire. To know about the validity and reliability of the instrument, the writer made some try out. Only a few students can resist the temptation to watch English movies on television. The students are proved to have a high intensity of watching English movie on television. Generally, most of the students spend much time to watch the programs. The good level of the students' vocabulary test result reflects the students' interest in English as a subject in school. Furthermore, based on the vocabulary test, students' level of vocabulary acquisition is in the high level. It can be interpreted that the students, on the average, are able to do more than 50% of all the items being tested.